Degradation of cIAPs contributes to hepatocyte lipoapoptosis - Akazawa, Yuko (American Physiological Society, 2013)
Hepatocyte apoptosis is a hallmark of nonalcoholic steatohepatitis. We have previously observed that the saturated free fatty acids (FFAs) induce hepatocyte apoptosis in part via a death receptor 5 (DR5)-mediated signaling pathway. Cellular inhibitor of apoptosis protein 1 and 2 (cIAP-1 and cIAP-2) proteins are potent inhibitors of death receptor-mediated apoptosis. However, the role of the cIAPs in FFA-mediated hepatocyte apoptosis is unexplored. Our aim was to determine whether cIAPs are dysregulated during hepatocyte lipoapoptosis. cIAP proteins underwent rapid cellular elimination following treatment with the saturated FFAs palmitate (PA) and stearate. In contrast, PA did not decrease cIAP-1 and cIAP-2 mRNA expression in the cells. Degradation of cIAPs was dependent on their E3-ligase activity, suggesting that cIAPs undergo autoubiquitination that leads to proteasomal degradation. Huh-7 cells stably expressing shRNA targeting cIAP-1, but not cIAP-2, displayed enhanced sensitivity to PA-mediated apoptosis. Incubation with the SMAC mimetic JP1584, which induces rapid degradation of cIAPs, also enhanced PA-mediated apoptosis. Hepatocytes isolated from DR5 knockout mice exhibited reduced apoptosis following treatment with PA plus JP1584, implying that degradation of cIAPs sensitizes to DR5-mediated cell death pathways. A decrease of cIAP-1 was also observed in tissue from patients with nonalcoholic steatohepatitis compared with normal obese subjects. Collectively, these results implicate proteasomal degradation of cIAPs by FFA as a mechanism contributing to hepatocyte lipoapoptosis.